Assessing the Potential Value and Mechanism of Kaji-Ichigoside F1 on Arsenite-Induced Skin Cell Senescence. (11th January 2022) - Zeng, Qibing; Du, Sufei; Xu, Yuyan; Yang, Fan; Wu, Liping; Wang, Nanlan; Zhang, Shuling; Wei, Shaofeng; Wang, Guoze; Zhang, Shuai; Lu, Hongguang; Luo, Peng
Abstract : Chronic exposure to inorganic arsenic is a major environmental public health issue worldwide affecting more than 220 million of people. Previous studies have shown the correlation between arsenic poisoning and cellular senescence; however, knowledge regarding the mechanism and effective prevention measures has not been fully studied. First, the associations among the ERK/CEBPB signaling pathway, oxidative stress, and arsenic-induced skin cell senescence were confirmed using the HaCaT cell model. In the arsenic-exposed group, the relative mRNA and protein expressions of ERK/CEBPB signaling pathway indicators (ERK1, ERK2, and CEBPB), cell cycle-related genes ( p21, p16 INK4a ), and the secretion of SASP (IL-1 α, IL-6, IL-8, TGF- β 1, MMP-1, MMP-3, EGF, and VEGF) and the lipid peroxidation product (MDA) were significantly increased in cells (P < 0.05 ), while the activity of antioxidant enzyme (SOD, GSH-Px, and CAT) was significantly decreased (P < 0.05 ), and an increased number of cells accumulated in the G1 phase (P < 0.05 ). Further Kaji-ichigoside F1 intervention experiments showed that compared to that in the arsenic-exposed group, the expression level of the activity of antioxidant enzyme was significantly increased in the Kaji-ichigoside F1 intervention group (P < 0.05 ), but the indicators of ERK/CEBPB signaling pathway, cell cycle-related genes, and SASP were significantly decreased (P < 0.05 ), and the cell cycle arrest relieved to a certain extent (P < 0.05 ). Our study provides some limited evidence that the ERK/CEBPB signaling pathway is involved in low-dose arsenic-induced skin cell senescence, through regulating oxidative stress. The second major finding was that Kaji-ichigoside F1 can downregulate the ERK/CEBPB signaling pathway and regulate the balance between oxidation and antioxidation, alleviating arsenic-induced skin cell senescence. This study provides experimental evidence for further understanding of Kaji-ichigoside F1, a natural medicinal plant that may be more effective in preventing and controlling arsenic poisoning.